BUSINESS MANAGEMENT: TIPS FOR SUCCESSFULLY MANAGING COMPANIES, INCLUDING PLANNING, FINANCIAL CONTROL, AND TEAM MANAGEMENT - Elva, Andreia Alves da Silva (Revista Sistemática, 2021)
Effective business management is fundamental to achieving organizational success in an increasingly dynamic and competitive global environment. This article explores three critical pillars of successful management: strategic planning, financial control, and team leadership. Strategic planning provides organizations with direction and adaptability through the continuous alignment of goals with internal and external conditions. Financial control ensures the efficient allocation and monitoring of resources, supporting operational stability and long-term growth. Effective team management, particularly through transformational leadership, fosters collaboration, motivation, and employee retention. The integration of these elements into a holistic management approach is presented through a conceptual flowchart, emphasizing their interdependence and cumulative impact. By adopting evidence-based and adaptive practices, companies can enhance innovation, resilience, and sustained competitive advantage.